Exploring the specific features of interfacial enzymology based on lipase studies - Aloulou, Ahmed; Rodriguez, Jorge A.; Fernandez, Sylvie; van Oosterhout, Dirk; Puccinelli, Delphine; Carrière, Frédéric (Biochimica et biophysica acta, 2006)
Many enzymes are active at interfaces in the living world (such as in the signaling processes at the surface of cell membranes, digestion of dietary lipids, starch and cellulose degradation, etc.), but fundamental enzymology remains largely focused on the interactions between enzymes and soluble substrates. The biochemical and kinetic characterization of lipolytic enzymes has opened up new paths of research in the field of interfacial enzymology. Lipases are water-soluble enzymes hydrolyzing insoluble triglyceride substrates, and studies on these enzymes have led to the development of specific interfacial kinetic models. Structure–function studies on lipases have thrown light on the interfacial recognition sites present in the molecular structure of these enzymes, the conformational changes occurring in the presence of lipids and amphiphiles, and the stability of the enzymes present at interfaces. The pH-dependent activity, substrate specificity and inhibition of these enzymes can all result from both “classical” interactions between a substrate or inhibitor and the active site, as well as from the adsorption of the enzymes at the surface of aggregated substrate particles such as oil drops, lipid bilayers or monomolecular lipid films. The adsorption step can provide an alternative target for improving substrate specificity and developing specific enzyme inhibitors. Several data obtained with gastric lipase, classical pancreatic lipase, pancreatic lipase-related protein 2 and phosphatidylserine-specific phospholipase A1 were chosen here to illustrate these specific features of interfacial enzymology.